Emission of hf radiation in n+n(x)n+ gaas devices under crossed electric and magnetic fields - Tiwari S.C. (My University, 2025)
Physical arguments are presented to investigate the possibility of altering Landau levels by varying the doping density in the active n-layer in sandwiched n+n(x)n+ structures. Energy eigenvalues obtained from the solution of the Schrod-inger equation provide the frequency range of possible radiation emission. © 1986, The Institution of Electrical Engineers. All rights reserved.